The spectacular few : prisoner radicalization and the evolving terrorist threat - Hamm, Mark S. (Alternative criminology series., 2013)
"Mark Hamm is, without doubt, the world's leading expert on prison radicalization. Based on decades of research, this book presents a nuanced and sophisticated picture, . Beautifully written, it is the most complete, and the most empirically rigorous, account of this phenomenon to date. A must read for anyone interested in homegrown radicalization."--Peter Neumann, Director of the International Centre for the Study of Radicalisation (ICSR), King's College London The Madrid train bombers, shoe-bomber Richard Reid, al-Qaeda in Iraq, and the 9/11 attacks-all were led by men radicalized behind ba